Comparing First-Order Microscopic and Macroscopic Crowd Models for an Increasing Number of Massive Agents. (20th March 2016) - Corbetta, Alessandro; Tosin, Andrea
Abstract : A comparison between first-order microscopic and macroscopic differential models of crowd dynamics is established for an increasing numberN of pedestrians. The novelty is the fact of considering massive agents, namely, particles whose individual mass does not become infinitesimal whenN grows. This implies that the total mass of the system is not constant but grows withN . The main result is that the two types of models approach one another in the limitN → ∞, provided the strength and/or the domain of pedestrian interactions are properly modulated byN at either scale. This is consistent with the idea that pedestrians may adapt their interpersonal attitudes according to the overall level of congestion.